Intention to adopt Industry 4.0 technologies among small and medium enterprises in the Malaysian dairy manufacturing industry - Saeedi, S. A. W.; S., Juwaidah; Kelly, W. K. S. (Rynnye Lyan Resources, 2022)
Small and medium enterprises (SMEs) are one of the key economic growth engines which play vital roles in Malaysia’s economy. In the manufacturing sector, SMEs are considered the backbone of industrial development. Presently, the dairy manufacturing industry is one with high potential. Technology is one of the enablers that can assist companies to improve their performances. Presently, SMEs are still hesitant to embrace and adopt new technology. The fundamental objective of this study was to identify the determinants of the intention to adopt Industry 4.0 technologies among SMEs in Malaysian. Data were collected from 114 managers of Small and Medium Enterprises (SMEs) and was analysed using SPSS. The findings from multiple regression revealed that the intention of SMEs to adopt Industry 4.0 Technologies was positively influenced by perceived usefulness (PU), perceived ease of use (PEU), subjective norm (SN), perceived behaviour control (PBC) and attitude (Att). Attitude had partial mediation effects on both relationships between PU and intention. It also has relationships between PEU and intention in adopting Industry 4.0 Technologies. The paper concludes and supports the assumptions of two theories - Theory of Planned Behaviour (TPB) and Technology Acceptance Model (TAM). This study contributes to enhancing managers and higher authority of SMEs in deciding the future course of their manufacturing firms and policymakers in mapping out plans for Malaysian SMEs in the dairy manufacturing industry.